Endothelin-1 in subarachnoid hemorrhage: an acute-phase reactant produced by cerebrospinal fluid leukocytes - Faßbender, Klaus; Knorr, Britta; Rossol, Siegbert; Bertsch, Thomas; Schmeck, Joachim; Schütt, Sandra; Fritzinger, Michael; Horn, Peter; Vajkoczy, Peter; Wendel-Wellner, Martina; Ragoschke-Schumm, Andreas; Kühl, Sandra; et al. (Stroke, 2000)
BACKGROUND AND PURPOSE: The most potent vasoconstrictor known, endothelin-1, is currently considered to mediate cerebral vasospasm in subarachnoid hemorrhage (SAH), which can cause delayed cerebral ischemia. In our study, we performed clinical and in vitro experiments to investigate the origin and the mechanisms of the secretion of endothelin-1 in SAH. - METHODS: Endothelin-1 and markers of inflammatory host response (interleukin [IL]-1ss, IL-6, and tumor necrosis factor-alpha) were comparatively quantified in the cerebrospinal fluid (CSF) of SAH patients and control subjects, and concentrations were related to clinical characteristics. Furthermore, mononuclear leukocytes isolated from the CSF of SAH patients and control subjects were analyzed regarding their mRNA expression of endothelin-1 and inflammatory cytokines. Finally, complementary in vitro experiments were performed to investigate whether coincubation of blood and CSF can trigger leukocytic mRNA expression and release of these factors. - RESULTS: Activated mononuclear leukocytes in the CSF of SAH patients synthesize and release endothelin-1 in parallel with known acute-phase reactants (IL-1ss, IL-6, and tumor necrosis factor-alpha). Complementary in vitro experiments not only further confirmed this leukocytic origin of endothelin-1 but also showed that aging and subsequent hemolysis of blood is sufficient to induce such endothelin-1 production. - CONCLUSIONS: The demonstration that endothelin-1 is produced by activated CSF mononuclear leukocytes suggests that subarachnoid inflammation may represent a therapeutic target to prevent vasospasm and delayed cerebral ischemia after SAH.
Gesehen am 20.07.2022